A COMPARISON OF EMERGENCY PREPAREDNESS AND MEDICAL COVERAGE BETWEEN HIGH SCHOOL AND CLUB SPORT COACHES. Issue 3 (31st March 2019) - Post, Eric G.; Schaefer, Dan; Biese, Kevin M.; Cadmus-Bertram, Lisa; Watson, Andrew; McGuine, Timothy A.; Brooks, Alison; Bell, David
BACKGROUND: Recent studies have demonstrated that a large population of high-school aged athletes participate on club sport teams. Studies have documented emergency preparedness and medical coverage standards in the high school athletic setting. However, similar examinations do not exist for youth club sport teams. PURPOSE: To determine if differences in emergency preparedness and medical coverage exist between high school team coaches and high school-aged club team coaches. A secondary purpose was to compare emergency training characteristics between high school and club coaches. METHODS: A total of 769 coaches (female N=266, 34.6%, age: 41.0±11.5 years) completed an anonymous online questionnaire regarding their emergency preparedness and training. Coaches from 3 sports were surveyed (basketball N=290, volleyball N=256, soccer N=223). The questionnaire consisted of 1) demographics and information regarding the teams that the respondent coaches, 2) emergency preparedness factors such as automated external defibrillator (AED) availability, emergency action plan (EAP) awareness, and medical coverage, and 3) emergency care training requirements (CPR, AED, first aid). Chi-square tests were used to compare response frequencies to various emergency preparedness questions between high school and club coaches. RESULTS: Overall, 64.6% (N=497) respondents were coaches of a high school team, and 35.4% (N=272) were coaches of a club team with high school-aged athletes. High school coaches were more likely than club coaches to be aware of the EAP for their practice venue (83.9% vs. 54.4%, p<.001), but most coaches in both categories had not practiced their EAP in the past 12 months (70.0% vs. 68.9%, p=.54). During competitions, high school coaches were more likely than club coaches to be aware of the EAP (47.5% vs. 37.1%, p=.02). However, the majority of coaches in each category reported that they were never aware of EAPs during competition. High school coaches were more likely than club coaches to 1) have an AED available at practice (87.9% vs. 58.8%, p<.001), 2), to report that athletic trainers were responsible for medical care at practices (31.2% vs. 8.8%, p<.001) and competitions (57.9% vs. 31.2%, p<.001), and 3) to be required to have CPR, AED, or first aid training (p<.001). Nearly all (98.8%) high school coaches were required to have CPR training, and overall, 58.6% of high school coaches were required to have training in all 3 categories (CPR, AED, first aid) compared to 23.9% of club coaches (p<.001). CONCLUSIONS: High school sport coaches displayed greater levels of emergency preparedness and training compared to coaches of high school-aged club teams. Significant attention and effort is needed to improve emergency preparedness and medical coverage at the club sports level among basketball, soccer, and volleyball coaches.